Quand les civils maintiennent l’ordre. Configurations vigilantes à Istanbul - Elise Massicard (Revue des Mondes Musulmans et de la Méditerranée)
Abstract: Since the 2000s various practices have emerged in the Tophane district of Istanbul relating to the maintenance of public order by civilians. These range from political violence and steps to tackle criminality to broader action to police public morality. Referring to them as "vigilante configurations" captures their fluidity whilst recognizing that they are comparatively structured and lent coherence by references to role models and social imaginaries. These crusades are conducted by local moral entrepreneurs operating with a fair degree of autonomy. In this the situation differs from other Middle Eastern contexts where the widespread existence of informers indicates that such movements are initiated from above. The practices in Tophane are tolerated and discreetly encouraged even due to shared political affinities with those in authority. This sets them apart from left-wing civilian initiatives to maintain public order in other districts of Istanbul, which are more severely repressed.